Evaluation of health financial protection policies through cost control and strengthening of JKN benefits: A literature review - Salsabila Firdausi; Evita Mutiara; Siti Rahima Kiram; Riswandy Wasir (Indonesian Journal of Health Science, 2026)
The National Health Insurance (JKN) has increased population coverage in Indonesia through financial protection determined by cost control, service payment governance, and benefit design. Its implementation has not completely eliminated the financial burden on households, with high out-of-pocket (OOP) spending on healthcare services and the associated risk of catastrophic health expenditure (CHE). This study aims to map the drivers of OOP spending and the risk of CHE, as well as strategies for improving financial protection. The method used is a literature review through searching articles obtained from several databases, namely Google Scholar, Garuda, Sciencedirect, Scopus, and Pubmed between 2017 and 2026. The results of the study indicate that JKN participation has proven effective in reducing OOP health expenditure by households, contributing to a reduced risk of CHE. However, the risk of CHE is still influenced by various other factors, such as the number of family members, high utilization of healthcare services, and limited healthcare facilities. Strengthening strategic purchasing, increasing benefits and equal access to healthcare services, and sustainable JKN financing are needed to improve financial protection. Thus, JKN has a role in reducing OOP expenditure which has an impact on reducing the risk of CHE, but financial protection is not yet fully optimal so that cost control and strengthening of JKN benefits are needed.